PENGARUH PENGGUNAAN TEKNIK COPY THE MASTER TERHADAP KETERAMPILAN MENULIS TEKS BIOGRAFI SISWA KELAS X SMAN 1 PAINAN PESISIR SELATAN - Ena Noveria, Tika Harnila, Abdurrahman, (Universitas Negeri Padang, 2017)
The purpose of this research are (1) to describe writing biografical text on the student SMAN 1 grade X Painan Pesisir Selatan before using copy the master technique (2) to describe writing biografical text on the student SMAN 1 grade X Painan Pesisir Selatan after using copy the master technique. (3) to describe the effect of using copy the master tecqnique on writing skills biografical text on the student SMAN 1 grade X Painan Pesisir Selatan. Based on data analysis, the used copy the master technique effect the skills of writing biografical text on the student SMAN grade X Painan Pesisir Selatan.Â Kata kunci : pengaruh, teknik Copy the Master, keterampilan menulis teks biografi